Pengembangan Pariwisata Fasilitas Akomodasi Berkelanjutan di Kecamatan Medan Barat - Amelia, Amelia; Saragih, Rehulina; Wisdianti, Dara (Jurnal Teknik dan Teknologi Indonesia, 2025)
Medan City possesses significant tourism potential with great opportunities for development, particularly in the Medan Barat District. Although this area is already equipped with various public and tourism-supporting facilities, several historical tourist attractions still lack adequate amenities due to land limitations. This research aims to design the development of a new tourism area in Medan Barat, specifically on Jalan Tanjung Mulia, which is capable of boosting local economic growth, preserving the environment, and serving as an integrated recreational destination for the public. This study utilizes a descriptive qualitative method, outlining and analyzing both primary and secondary data to formulate an area development concept. The results of the study propose the design of a multifunctional recreational park integrated with a Micro, Small, and Medium Enterprises (MSME) area at the front of the site. This park is designed to facilitate various relaxing activities after a tiring day of work or during holidays, such as exercising, picnicking, and culinary tourism. Through this development, it is hoped that the area can overcome the limitations of existing tourism facilities while simultaneously providing a positive impact on visitor satisfaction and the economy of the community.